Map of North America : engraved to illustrate Mitchell's school and family geography - Young, J. H. (James Hamilton) (S. Augustus Mitchell, 1858)
Map shows "Dr. Kane's" explorations; major cities and physical features for the United States, Russian America [Alaska], British America, Mexico, Central America, the West Indies, and Greenland; areas of Native Ameican habitation; Antarctic continent with discovery dates and explorers' names on verso. Relief shown by hachures. Scale [ca. 1:35,000,000].